DARIC: A Data Reuse-Friendly CGRA for Parallel Data Access via Elastic FIFOs - Liu, Dajiang; Mou, Di; Zhu, Rong; Zhuang, Yan; Shang, Jiaxing; Zhong, Jiang; Yin, Shouyi (2023 60th ACM/IEEE Design Automation Conference (DAC), 2023)
Coarse-Grained Reconfigurable Arrays (CGRAs) are a promising architecture for data-intensive applications. For parallel data accesses, uniform memory partitioning is usually introduced to CGRA for better pipelining performance. However, uniform memory partitioning not only suffers from a local minimum, but also introduces non-negligible overhead for banking function, which may greatly degrade the performance of CGRA. To this end, this paper introduces non-uniform memory partitioning and proposes a data-reuse-friendly CGRA (DARIC). With well elaborated configurable bank groups cooperated with register chains, elastic FIFOs can be achieved for non-uniform memory partitioning. Based on the resource graph of DARIC, a mapping algorithm supporting path sharing is proposed. Finally, the experimental results show that DARIC can achieve 2.35 × throughput and 2.59 × energy efficiency while having even less area and power overhead, as compared to the state-of-the-art.